Perception of leakage: data from the Ostomy Life Study 2019. (9th December 2021) - Down, Gillian; Vestergaard, Martin; Ajslev, Teresa Adeltoft; Boisen, Esben Bo; Nielsen, Lene Feldskov
Abstract : Background: Leakage is a common problem for people with a stoma. Aim: To investigate how people with a stoma and stoma care nurses perceive different patterns of effluent under the baseplate. Methods: The Ostomy Life Study 2019 included a user survey and a nurse survey covering experiences of leakage and the perception of leakage. Findings: Most people with a stoma perceived effluent reaching outside the baseplate as leakage (88–90%), whereas effluent close to the stoma only was not perceived as leakage by the majority (81–91%). Effluent covering major parts of the baseplate was perceived as leakage by most respondents with a colostomy or ileostomy (83%), whereas fewer respondents with a urostomy perceived this as leakage (57%). Most of the nurses (70%) did not perceive effluent close to the stoma as leakage. Conclusion: This study revealed that effluent confined to the area next to the stoma is generally not perceived as leakage.